Compatibility studies between propafenone and selected excipients used in the development of controlled release formulations - Shahe, Mahammad S; Chetty, Madhusudhana; Murthy, KV Ramana (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study was to evaluate the compatibility of propafenone HCl (PFH) with the selected excipients used in a controlled drug delivery system. The studies were conducted by an isothermal stress test method. The differential scanning calorimetry (DSC) and high-performance liquid chromatography techniques were used as tools to assess the compatibility of the drug with the selected excipients. Complementary techniques such as powder X-ray powder diffractometry (pXRD) and fourier transform infrared (FTIR) spectroscopy were used to assist in the interpretation of the DSC results. On the basis of the DSC results, the drug was found to be compatible with gum kondagogu (GKG), chitosan, polyelectrolyte complex of GKG and chitosan, HPMC K100M, carbopol 934P, BenecelÂ® and A-tabÂ®. Some degree of interaction was observed with lactose monohydrate; however, the additional studies using FTIR spectroscopy and pXRD confirmed that PFH is compatible with lactose monohydrate.